Belajar Nilai Moral Melalui Drama Peraga: Penguatan Karakter Anak Melalui Teater Mini - Edo Dwi Cahyo; Asep Yudianto; Laili Ulfa (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2025)
This community service program aimed to strengthen moral character among elementary school students through drama-based learning. Conducted at MIN 3 Metro, the program involved 25 fifth-grade students and utilized participatory methods, including role-playing, scriptwriting, and drama performances. The activities were designed to enhance emotional intelligence, moral reasoning, and understanding of Pancasila values through experiential learning. Results showed significant improvements: a 72% increase in emotional recognition skills, an 80% reduction in bullying incidents, and 92% of student groups successfully integrating Pancasila principles into their scripts. Qualitative observations revealed profound personal transformations, such as increased confidence in shy students and improved conflict-resolution skills. The program also fostered unexpected outcomes, including the discovery of hidden talents and stronger peer collaboration. Key success factors included student-centered creative processes, simple technological integration for reflection, and strong collaboration with teachers. Challenges such as time constraints were overcome through innovative solutions like "whisper theater" techniques. This initiative demonstrates that drama-based methods can effectively bridge the gap between moral knowledge and real-life application, suggesting its potential for broader implementation in character education programs.